Methicillin-Resistant Staphylococcus aureus: The Shifting Landscape in the United Arab Emirates - Syrine Boucherabine; Rania Nassar; Lobna Mohamed; Maya Habous; Anju Nabi; Riyaz Amirali Husain; Mubarak Alfaresi; Seema Oommen; Hamda Hassan Khansaheb; Mouza Al Sharhan; Handan Celiloglu; Mubarak Hussain Raja; et al. (Antibiotics)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a significant burden globally, particularly in the Arabian Gulf region. The United Arab Emirates (UAE) has experienced rising MRSA prevalence, with increasing diversity in the clonal complexes (CCs) identified. The COVID-19 pandemic, with its increased hospitalization rates and antibiotic use, may have further influenced MRSA’s genetic evolution and epidemiology in the country. Methods: To investigate this influence, genomic profiling of 310 MRSA clinical isolates collected between February and November 2022 was performed using a DNA microarray-based assay. Results: Isolates were assigned to 22 clonal complexes and 72 distinct strain assignments. The predominant clonal complexes were CC5, CC6, CC361, CC22, CC1, and CC8. Community-acquired MRSA lineages were dominant, with only one healthcare-associated MRSA lineage isolate identified. Upward trends of CC1153 were observed along with rare CCs, such as CC121-MRSA and CC7-MRSA, with the latter being reported for the first time in the Arabian Gulf region. The presence of pandemic strains USA300 CC8-MRSA-[IVa + ACME1] and CC8-MRSA-IV strains were also observed, including variants lacking Panton–Valentine leukocidin (pvl) genes and missing tst1 or enterotoxin genes. The PVL-negative CC772-MRSA-V/VT was identified, representing its first report in the UAE. A novel variant, CC361-MRSA-IV (tst1+/PVL+), was identified. Pvl genes were observed in 36% of the isolates, primarily from skin and soft tissue infections, while fusC (SCC-borne fusidic acid resistance) was identified in 13% of the isolates. Conclusions: The findings highlight the ongoing evolution of MRSA in the UAE, with the persistence and emergence of diverse and rare clonal complexes, driving the need for continuous genomic surveillance.